Analisis Mencegah Potensi Bahaya Dengan Metode Hiradc di Unit Operation & Maintenance MPS 3 PT APS - Nando, M. Eggy Zulmi Zulmi; Farida, Farida (Proceeding Mercu Buana Conference on Industrial Engineering, 2020)
The aviation company PT Angkasa Pura Solusi has a business unit of Operation & Maintenance work with activities to carry out generator maintenance, Ground Tank maintenance, Crane & Lift maintenance, transformer maintenance, etc., where each job has a high potential hazard at PT APS. Potential hazards can occur due to the working environment conditions and understanding of K3 workers is still lacking. Therefore, it is necessary to carry out risk management to identify hazards and control them using the HIRADC (Hazard Identification Risk Assessment and Determining Control) method. The results showed that there were 4 highest potential hazard risks in each MPS 3 Operation & Maintenance job, including electrocution, pinching, falling from a height and fire, where the potential hazards must be carried out risk control by inspecting equipment when going to work, using complete PPE, using full body hardness when working at height, team Safety Operation & Maintenance MPS 3 updates JSA and HIRADC, adds deficient SOPs and installs safety instructions at each work site